Abstract WP215: Stroke Without Ischemic Lesions On The Initial Diffusion Weighted Image ~Fukuoka Stroke Registry - Fujimoto, Shigeru; Mezuki, Satomi; Matsuki, Takayuki; Jinnouchi, Juro; Ishitsuka, Takao; Kitazono, Takanari (Stroke, 2013)
Abstract only Background & Purpose: Diffusion weighted image (DWI) is indispensable in the early diagnosis of acute ischemic stroke. However, DWI cannot always detect an acute ischemic lesion. We investigated the clinical features and outcome of stroke patients without an ischemic lesion on the initial DWI. Subjects & Methods: Among the consecutive 3062 patients with sudden neurological deficits who were admitted to the 7 stroke centers in Fukuoka prefecture Japan within 24 hours after the symptom onset, 1731 patients with neurological deficits duration of 24 hours or more and pre-stroke modified Rankin scale (mRS) of 0 or 1 were included in the present study. All patients underwent MRI studies including DWI. We investigated clinical features, a neurological deterioration (a NIHSS score worsening of ≥1-point), and stroke recurrence. Results: Among 1731 patients, 102 (5.9%) had no ischemic lesions on DWI (DWI-negative Group), and other 1629 had ischemic lesions on DWI (DWI-positive Group). Atrial fibrillation (16.7% vs 29.2%, p=0.0064) and intracranial or extracranial cerebral artery stenosis of ≥50% in diameter (16.7% vs 36.3%, p<0.0001) were less frequent, and the initial NIH stroke scale score was lower (3.2±2.8 vs 5.8±5.9, p<0.0001) in the DWI-negative than the DWI-positive Group. Analysis on 285 patients who underwent transesophageal echocardiography (TEE), there was no significant differences in the frequency of complicated aortic arch lesions or patent foramen ovale between both groups. Stroke recurrence during the hospital days was relatively less frequent in the DWI-negative than the DWI-positive Group (2.9% vs 4.2%), however, stroke recurrence during 3 months after the onset was relatively more frequent in the DWI-negative than the DWI-positive Group (7.8% vs 6.2%). A good outcome (modified Rankin scale of 0 or 1) on 3 months after the onset was more frequent in the DWI-negative than the DWI-positive Group (73.1% vs 57.7%, p=0.0035). Conclusions: Although a good outcome was more frequent in the DWI-negative than the DWI-positive Group, a stroke recurrence was not rare in the DWI-negative Group. Evaluations for the etiology of stroke, such as TEE, were required even in the stroke patients without ischemic lesions on the initial DWI.